Association of Framingham Steatosis Index with Albuminuria: A cross-sectional study - Dongli Huang; Huan Zou; You Zhang (PLoS ONE, 2025)
Background The Framingham Steatosis Index (FSI) is a diagnostic indicator of hepatic steatosis. Although prior studies have established associations between hepatic steatosis and chronic kidney disease (CKD) and between FSI and CKD, the association between FSI and proteinuria remains unexplored. This study investigated the association between FSI and albuminuria, addressing this research gap. Patients and methods Data were obtained from the National Health and Nutrition Examination Survey (NHANES) database. The association between FSI and albuminuria was examined using multivariable logistic regression and stratified analyses. Nonlinearity was assessed using smoothing curves, and inflection points were located with a recursive algorithm. Subgroup analyses were conducted to evaluate the consistency of the association between FSI and albuminuria across different strata. Finally, propensity score matching (PSM) was applied to reduce potential confounding and enhance the robustness of the findings. Results In model 3, which adjusted for all covariates, the odds ratio (OR) for the association between FSI and albuminuria was 1.13 (95% CI: 1.09–1.18). Smooth curve fitting demonstrated a U-shaped relationship between FSI and albuminuria. Threshold analysis identified an inflection point at an FSI value of −3.22 to further characterize this relationship. Subgroup analyses showed directionally consistent associations across strata. The U-shaped relationship between FSI and albuminuria remained robust after applying PSM. Conclusion Our study identified a U-shaped relationship between FSI and albuminuria.